2015
DOI: 10.1590/1413-81232015203.04332013
|View full text |Cite
|
Sign up to set email alerts
|

Construção de instrumentos de medida na área da saúde

Abstract: Construção de instrumentos de medida na área da saúdeConstruction of measurement instruments in the area of health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
338
0
390

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 436 publications
(728 citation statements)
references
References 36 publications
0
338
0
390
Order By: Relevance
“…(11) The steps for development of instruments recommended by the literature were followed in order to ensure the construction of a reliable tool. (14) The participation of professionals in the fields of healthcare, applied linguistics and statistics at this stage was important to assure proper selection and organization of items and domains, in addition to the analysis of the potential data in the test phase. (14,17,18) As a result of the validation performed by the health professionals, the Compasso was considered a protocol with relevant and valuable content regarding the promotion of adherence to self-care practices in diabetes mellitus type 2, a factor that was evidenced by the mean CVI of 0.96, recommended as an acceptable value in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(11) The steps for development of instruments recommended by the literature were followed in order to ensure the construction of a reliable tool. (14) The participation of professionals in the fields of healthcare, applied linguistics and statistics at this stage was important to assure proper selection and organization of items and domains, in addition to the analysis of the potential data in the test phase. (14,17,18) As a result of the validation performed by the health professionals, the Compasso was considered a protocol with relevant and valuable content regarding the promotion of adherence to self-care practices in diabetes mellitus type 2, a factor that was evidenced by the mean CVI of 0.96, recommended as an acceptable value in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…(14) The participation of professionals in the fields of healthcare, applied linguistics and statistics at this stage was important to assure proper selection and organization of items and domains, in addition to the analysis of the potential data in the test phase. (14,17,18) As a result of the validation performed by the health professionals, the Compasso was considered a protocol with relevant and valuable content regarding the promotion of adherence to self-care practices in diabetes mellitus type 2, a factor that was evidenced by the mean CVI of 0.96, recommended as an acceptable value in the literature. (14,15) The content of Compasso questions include findings from other studies in which the individuals reported that the barriers for the practice of selfcare are related to psychosocial, economic and behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations